Students' Historical Awareness of the Character and Example of Sunan Kudus at MA Qudsiyyah Kudus - Firdaus, Aufa Hasan; Purnomo, Arif; Ahmad, Tsabit Azinar (Universitas Negeri Semarang, 2021)
This research wishes to reveal some points like explaining the process of implementing historical awareness towards the figurative of Sunan Kudus in history subject in MA Qudsiyah Kudus, explain the factors that influence the degree of historical awareness that students have towards the figurative of Sunan Kudus in history subject in MA Qudsiyah Kudus, and explain the facilities that inseminate in the effort of implementing the historical awareness towards the figurative of Sunan Kudus in history subject in MA Qudsiyah Kudus. This research used the qualitative method and phenomenology approach as a descriptive approach. The results of this study indicate that the planting of historical awareness of the example and figure of the Sunan Kudus in the study of the history of Islamic culture in the Holy Quran Qudsiyyah has been proven, as evidenced by the Learning Implementation Plan and Syllabus in the 2013 Curriculum, the implementation of learning, evaluation, and awareness of student history shown in large part from the results. Student interviews are understood. Some factors influence students' historical awareness, among others, from the competence of history teachers, existing learning, and their environment. The facilities used to plant historical awareness have supported education and extracurricular resources.